Evaluation of sonographic endometrial patterns and endometrial thickness as predictors of ectopic pregnancy. Issue 1 (11th November 2016) - Yadav, Poonam; Singla, Anshuja; Sidana, Anu; Suneja, Amita; Vaid, Neelam B.
Abstract: Objective: To evaluate whether endometrial patterns and thickness could be used for the prediction of ectopic pregnancy (EP). Methods: A prospective study was conducted in a center in India between October 2007 and December 2008. It included 100 women with an early pregnancy confirmed by urine pregnancy testing but for whom an intrauterine gestational sac was not visualized on transvaginal ultrasonography (TVS). The women were divided into an EP group and an intrauterine pregnancy (IUP) group depending on the final diagnosis. The endometrial pattern and endometrial thickness were determined by TVS. Sensitivity and receiver operating characteristic curve analyses were performed to determine the predictive value. Results: A heterogenous hyperechoic or trilaminar endometrial pattern was noted in 53 (77%) of 69 women in the EP group and 12 (39%) of 31 in the IUP group, and a homogenous hyperechoic pattern in 3 (4%) women in the EP group and 13 (42%) in the IUP group. An endometrial thickness of less than 9.8 mm was predictive of EP ( P <0.001), and an endometrial pattern other than homogenous hyperechoic had a sensitivity and a negative predictive value of 81.3% for the diagnosis of EP. Conclusion: Evaluation of endometrial thickness and pattern by TVS helps to identify women with a pregnancy of unknown location for close supervision. Abstract : Transvaginal ultrasonography evaluation of the endometrial thickness and pattern can help to identify women with a pregnancy of unknown location who should be closely monitored.